A SNP Genotyping Array for Hexaploid Oat. Issue 3 (1st November 2014) - Tinker, Nicholas A.; Chao, Shiaoman; Lazo, Gerard R.; Oliver, Rebekah E.; Huang, Yung‐Fen; Poland, Jesse A.; Jellen, Eric N.; Maughan, Peter J.; Kilian, Andrzej; Jackson, Eric W.
Abstract : Recognizing a need in cultivated hexaploid oat ( Avena sativa L.) for a reliable set of reference single nucleotide polymorphisms (SNPs), we have developed a 6000 (6K) BeadChip design containing 257 Infinium I and 5486 Infinium II designs corresponding to 5743 SNPs. Of those, 4975 SNPs yielded successful assays after array manufacturing. These SNPs were discovered based on a variety of bioinformatics pipelines in complementary DNA (cDNA) and genomic DNA originating from 20 or more diverse oat cultivars. The array was validated in 1100 samples from six recombinant inbred line (RIL) mapping populations and sets of diverse oat cultivars and breeding lines, and provided approximately 3500 discernible Mendelian polymorphisms. Here, we present an annotation of these SNPs, including methods of discovery, gene identification and orthology, population‐genetic characteristics, and tentative positions on an oat consensus map. We also evaluate a new cluster‐based method of calling SNPs. The SNP design sequences are made publicly available, and the full SNP genotyping platform is available for commercial purchase from an independent third party.